Pembangunan Sistem Rekam Medis Gigi Berbasis Web - Nadia Kusuma Putri; Bayu Priyambadha; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Identification victims of accidents or natural disasters can be done by examining the characteristics of the teeth. Examining the characteristic by teeth in victim identification is an accurate and easy method because teeth is the hardest part of body and has a lot of variation such as broken, filling, extraction, implant teeth, etc. However, there is a problem in identification victims using dental characteristics, that is incomplete medical dental records that can be used for victim identification. The facts there are still many dental clinics that do not perform the dental medical records according to the National Standard of Dental Medical Record because odontogram record takes longer time. This happened because dentists and nurses should draw symbols that match the patient's dental condition on an odontogram paper. Because of that, this research is aiming to build a web based dental medical record system so it can facilitate the dentist in performing dental medical records according to the National Standard Dental Medical Record. This research use prototyping model as a model in software development life cycle and built using CodeIgniter framework that support MVC (Model - View - Controller) and also using javascripst, jQuery, and Ajax to support the system to be more interactive. In the testing step, functional testing is done by using white box dan black box testing, and non-functional testing is done by using compactibility testing. From the test results on the functional system obtained that 100% valid or no errors in the system. While the non-functional testing system obtained results that the system can run well on two different browsers Chrome and Mozilla Firefox.